[Am(C5Me4H)3]: An Organometallic Americium Complex. (25th July 2019) - Goodwin, Conrad A. P.; Su, Jing; Albrecht‐Schmitt, Thomas E.; Blake, Anastasia V.; Batista, Enrique R.; Daly, Scott R.; Dehnen, Stefanie; Evans, William J.; Gaunt, Andrew J.; Kozimor, Stosh A.; Lichtenberger, Niels; Scott, Brian L.; et al.
Abstract: We report the small‐scale synthesis, isolated yield, single‐crystal X‐ray structure, 1 H NMR solution spectroscopy /solid‐state UV/Vis‐nIR spectroscopy, and density functional theory (DFT)/ab initio wave function theory calculations on an Am 3+ organometallic complex, [Am(C5 Me4 H)3 ] (1 ). This constitutes the first quantitative data on Am−C bonding in a molecular species. Abstract : Captain Americium : Die erste strukturelle Charakterisierung einer molekularen Am‐C‐Wechselwirkung wurde mit Standard‐Charakterisierungstechniken der synthetischen Chemie, einschließlich 1 H‐NMR‐ und UV/Vis/NIR‐Spektroskopie in Lösung, durchgeführt. Theoretische Modelle der elektronischen Struktur sind in ausgezeichneter Übereinstimmung mit den experimentellen Daten.